A new cathode material LiCu2O2 for secondary lithium batteries - Jacob, M. Milburn Ebenezer; Hassan, M S; Mohd Daud, Jamaluddin; Arof, Abdul Kariem (Ecole Polytechnique de Montreal, 2000)
A cathode material LiCu2O2 has been synthesized by the sol-gel method. The X-ray diffraction pattern of the material was matched with the JCPDS data from which it was inferred that the material is LiCu2O2. A cell was assembled with LiCu2O2 as the cathode material and Cu2O as the anode material. The cell characteristics show that on charging for 1.5 hr at 200 uA, the cell could only deliver 15% of its total capacity.